Paper product from Malaysian Bamboo - Buluh Semantan / Amran Shafie … [et al.] - Shafie, Amran; Ahmad Zaki, Junaiza; Mohd Hassan, Nurul Husna; Muhammed, Suhaimi; Ibrahim, Rushdan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Corrugated paper is currently being produced with additional of imported softwood pulps as their source of virgin pulps. Semantan bamboo has been identified as potential source of readily available raw material for such purpose. The pulping of semantan bamboo revealed that pulping condition with 15% alkali charge and 150°C cooking temperature leads to good paper properties. The paper tensile index was 87.71 Nm/g, bursting index was 6.94 kPa. m2/g, tearing index was 12.72 mN.m2/g and folding endurance was 613 double folds. After that, the bamboo pulp was mixed with recycle paper pulp and made into 120 gsm paper for corrugated paper manufacturing. The results revealed improved values with increasing bamboo percentage added to the recycle paper. Zero-span index and flat crush test for 2.5%, 5%, 7.5% and 10% bamboo added with recycle paper properties were 180.13,182.75,190.46 and 193.80 Nm/g and 179.67,184.6,192.78 and 205.13 N respectively. In conclusion, Semantan bamboo possesses great potential in enhancing the recycle paper properties; therefore this bamboo species serves as a good substitute for the current imported virgin softwood pulps